In Darwin's Wake, Where Am I? - Dennett, Daniel C. (Tufts Archival Research Center, 2005)
Dennett, Daniel C. "In Darwin's Wake, Where Am I?" Proceedings and Addresses of the American Philosophical Association 75, no. 2 (November 2001): 13-30.